Pengendalian Hama Terpadu pada Pertanaman Cabai dengan Fokus Aplikasi Bioinsektisida Berbahan Aktif Bacillus thuringiensis - Yulia Pujiastuti; Arsi Arsi; Suparman Suparman; Bambang Gunawan (PRIMA: Journal of Community Empowering and Services, 2024)
Integrated Pest Control in Chili Plantations with a Focus on Bioinsecticide Applications with Active Ingredients Bacillus thuringiensis. Bacillus thuringiensis is an entomopathogenic bacterium that plays important role in controlling plant pests. These bacteria can be propagated with agricultural waste media producing bioinsecticides. The use of bioinsecticides for controlling insect pests on chili plants was done through community service activities. The activity was carried out in Tanjung Baru Village, North Inderalaya Sub-district, Ogan Ilir Regency, South Sumatra, from August to October 2021. As one of the chili producing centers, farmers in Tanjung Baru Village grew chili almost all year round. Insects pests attacing chili plants were aphids, thrips, armyworms and fruit flies. Control is mostly done with synthetic insecticides, which are often mixed. Control activities focusing on the use of bioinsecticides with B. thuringiensis-based were carried out to overcome this problem. An initial demonstration plot was made for farmers to see the results of the experiment. The next stage farmers were given skills to make these bioinsecticides. To measure the success of the activity, a feedback survey was conducted amongfarmers. The survey results showed 80% of farmers were interested in using B. thuringiensis-based bioinsecticide and intended to use it. Regarding the skills of making bioinsecticides, more than 90% were interested in making their own, because waste materials as a medium for propagation were available in abundance. Chili farmers in Tanjung Baru Village can receive information from outsiders and showed a desire to change their old habit (use of chemical insecticides) to switch to biological control.